Global cytokine/chemokine profile identifies potential progression prediction indicators in hand-foot-and-mouth disease patients with Enterovirus A71 infections. (November 2019) - He, Yaqing; Feng, Zhuoying; Wang, Wei; Chen, Ying; Cheng, Jinquan; Meng, Jun; Yang, Hong; Wang, Yujie; Yao, Xiangjie; Feng, Qianjin; Chen, Long; Zhang, Hailong; et al.
Abstract: Objective: New clinical indicators are urgently needed for predicting the progression and complications of hand-foot-and-mouth disease (HFMD) caused by EV-A71 infections. Materials and methods: Serum specimens from 132 EV-A71 HFMD patients and 73 health children were collected during 2012–2014 in Shenzhen, China. The specific cytokines/chemokines were detected with a 274-human cytokine antibody array, followed by a 38-inflammation cytokine array, and further validated by ELISA. Results: Cytokines varied in different severity of EV-A71 HFMD patients. The ROC curve analysis revealed 5 serum cytokines with high sensitivity and specificity in predicting the disease progression. Eotaxin, IL-8 and IP-10 have showed high AUC values (0.90–0.95) for discrimination between the health controls and the patient group. The three cytokines showed high sensitivity (80–91%) and specificity (88–95%). MMP-8 had a high sensitivity and specificity to predict mild HFMD (100%, 100%). IL-1b and leptin discriminated the severe/critical group from the mild group (79% and 69% in sensitivity, 73% and 63% in specificity). Conclusions: Eotaxin, IP-10 and IL-8 could be potential indicators for predicting HFMD progression with EV-A71 infection. MMP-8 is a specific indicator for mild infection, while IL-1b and leptin display potential for predicting the severity and criticality.